Psychological well-being and workplace well-being on the mental health of seafarers in Indonesia - Ardhiana Puspitacandri; Moejiono Moejiono (University of Merdeka Malang, 2026)
This study investigates the influence of psychological well-being and workplace well-being on the mental health of Indonesian seafarers by examining both factors within a single model in the maritime work context. This approach provides a broader understanding of how personal psychological resources and workplace conditions are associated with mental health outcomes. Using a quantitative approach, data were collected from 124 active Indonesian seafarers through three validated instruments: the Depression Anxiety Stress Scale (DASS-42), the Workplace Well-Being Index (WWBI), and Ryff’s Psychological Well-Being Scale. Multiple linear regression analysis showed that psychological well-being (β = -1.126, p < 0.001) and workplace well-being (β = -0.475, p = 0.021) were significant predictors of psychological distress. Psychological well-being contributed 14.22 percent and workplace well-being contributed 6.17 percent to the explained variance, while both variables jointly accounted for 20.4 percent of the variation in psychological distress. Higher levels of psychological well-being and workplace well-being were associated with lower levels of depression, anxiety, and stress among seafarers. These findings highlight the importance of both individual psychological resources and workplace conditions in supporting seafarers’ mental health. The results suggest that efforts to improve mental health in the maritime sector should focus not only on strengthening psychological well-being but also on promoting supportive workplace environments.